Development Of Web-Based Flıpbooks On Anımal Adaptatıon To Theır Envıronment For Grade Vı Elementary School - Asidiqi, Deby Fauzi; Ratnasari, Dine Trio; Adiputra, Dede Kurnia; Heryadi, Yadi; Fadhliah, Euis (Elementary Teacher Education Program, Majalengka University, 2024)
This research is a research and development (Research and Development) using the ADDIE model (analysis, design, development, implementation, and evaluation). The data in this study consist of qualitative data and quantitative data. Qualitative data in the form of suggestions and comments from validators, teacher responses and student responses regarding the products developed. While quantitative data in the form of the results of expert validation questionnaires for media, materials, language, teacher response questionnaires and student response questionnaires. The subjects of this study were grade VI students of SDN 2 Narimbang Mulia. The data for this study were obtained through expert validation questionnaires, teacher response questionnaires, student response questionnaires, interviews and documentation. Then the data was analyzed to determine the level of validity and effectiveness of the product. The results of research and development based on the media validation questionnaire fall into the